2022
DOI: 10.1177/20503121221088100
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of semen analysis in male partners of infertile couples in Western Ethiopia: Retrospective cross-sectional study

Abstract: Objectives: This study assesses the pattern of semen analysis results in male partners of infertile couples at Gimbie Adventist Hospital, Western Ethiopia, 2021. Methods: A retrospective cross-sectional study on 131 semen samples of male partners of infertile couples was conducted at Gimbie Adventist Hospital from 5 September 2021 to 5 October 2021. All semen samples were processed and analyzed according to methods and standards outlined by the World Health Organization laboratory manual for the examination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Even though a re-analysis of this finding was based on the menstrual cycles, a similar result was also shown. These phenomena could be explained as follows: (1) many reasons might cause infertile in women, such as BMI, smoke (in men), maternal immune disorder, asthenozoospermia (from the male couple), and fallopian tube diseases ( 19 – 22 ). A single-time HSG with oil-based contrast agents might only improve some of these issues, including the maternal immune environment and flushing the tubules; apart from that, patients might also put forward some arrangements to cope with other infertile-related issues after HSG, such as losing weight, stopping smoking, and semen quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a re-analysis of this finding was based on the menstrual cycles, a similar result was also shown. These phenomena could be explained as follows: (1) many reasons might cause infertile in women, such as BMI, smoke (in men), maternal immune disorder, asthenozoospermia (from the male couple), and fallopian tube diseases ( 19 – 22 ). A single-time HSG with oil-based contrast agents might only improve some of these issues, including the maternal immune environment and flushing the tubules; apart from that, patients might also put forward some arrangements to cope with other infertile-related issues after HSG, such as losing weight, stopping smoking, and semen quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…About one-third had abnormal sperm count, which is below the WHO 2010 reference for semen analysis. [7] This proportion is also lower compared to the study of [8] where more than four-fifths were found to have abnormal sperm count. Almost 7 out of 10 respondents had abnormal (Athenospermia) progressive motility) which is more than the WHO 2010 reference of <32%.…”
Section: Discussionmentioning
confidence: 87%